White Christian Nationalism and Relative Political Tolerance for Racists. (20th March 2020) - Davis, Joshua T; Perry, Samuel L
Abstract: Recent studies demonstrate that white Americans who adhere to "Christian nationalism"―an ideology that idealizes and advocates a fusion of Christianity and American civic life―tend to hold authoritarian, exclusionary, and overtly prejudicial attitudes, particularly regarding ethno-racial minorities. We use data from the 1996 and 2014 General Social Surveys and consider relative political tolerance toward old-fashioned racists (i.e., persons who believe black Americans are genetically inferior) compared to other historically stigmatized groups, including anti-religionists, communists, militarists, and homosexuals. Viewing Christian identity as essential to American civic belonging is among the strongest predictors of whites' being politically intolerant of all stigmatized groups, racists included. However, when we examine relative tolerance toward racists compared to other stigmatized groups, white Christian nationalists show greater tolerance than other whites. This effect is distinct from personal religiosity which is associated with lower relative tolerance toward racists. Additionally, we find both time and gender moderate the association between white Christian nationalism and relative tolerance toward racists. Findings ultimately demonstrate that white Americans who adhere to Christian nationalism exhibit authoritarian tendencies―expressing lower tolerance for all groups considered―while making greater relative allowance for old-fashioned racists, who may be allies in the task of social control and coercion.